Hydrated calcium silicate fiber reinforced cement-based composite material and preparation method thereof
The C-S-H/PVA hybrid fibers prepared by using wet spinning technology in cement-based materials solve the brittleness problem of cement-based materials, significantly improve their toughness and durability, and ensure the safety and environmental benefits of building structures.
Patent Information
- Application Number
- CN202411329022.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
The brittleness of cement-based materials leads to prone to cracking and fracture during load-bearing, threatening the safety and stability of the building, and the prior art is difficult to effectively improve its toughness and durability.
Using polyvinyl alcohol (PVA) as organic template, nanosheet layer of hydrated calcium silicate (C-S-H) was introduced, and high-strength, high-toughness C-S-H/PVA hybrid fibers were prepared by wet spinning technology, and they were combined with cement-based The material is composited to enhance the bonding effect of fibers and matrix and improve the toughness and durability of the material.
It significantly improves the toughness and durability of cement-based composite materials, reduces the generation of cracks, reduces the heat conduction effect, and ensures the safety of building structures and economic and environmental benefits.
Smart Images

Figure CN119221148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a calcium silicate hydrate fiber cement-based composite material for achieving matrix toughening and a preparation method thereof. Background Art
[0002] As one of the important building materials, cement is widely used in various fields such as civil engineering and hydraulic engineering because of its advantages such as being workable for a certain period of time after adding water and mixing, and providing high strength for a long time after solidification and hardening. It has become the cornerstone of social infrastructure. With the increasingly harsh construction environment and the complexity of building structures, the country has put forward higher requirements for the strength, durability and safety of cement-based materials. Among them, the high brittleness of cement-based materials makes it easy to crack and break during the load-bearing process, resulting in structural damage, which is a key issue threatening the safety and stability of buildings.
[0003] To overcome this inherent defect, a variety of high-strength and high-toughness materials are added to the cement matrix in the hope of improving the toughness of the material. For example, the paper "Research Progress on the Application of Graphene Oxide in Cement-based Composites" records the potential of graphene oxide nano two-dimensional materials in improving toughness. For example, the invention patent with application number CN202311053429.2 discloses a method for preparing a super-tough shell-like layered structure cement-based composite material, which uses directional ice template method, vacuum negative pressure impregnation, multiple freeze-thaw cycles and other processes to fill PVA hydrogel into the pores of the cement skeleton.
[0004] Compared with expensive two-dimensional materials and complex layered structure designs, fiber materials can simplify construction processes and reduce costs on the basis of improving the toughness of cement-based materials, and have been widely used. In order to enhance the toughening potential of fiber materials, the weak bonding between fiber materials and cement matrix has become the key to enhancement. For example, the paper "Grafting SiO2nanoparticles on polyvinyl alchohol fibers to enhance the interfacial bonding strength with cement" records that grafting nano-silica on PVA fibers effectively enhances the bonding between fibers and cement matrix in simulation calculations, and achieves toughness improvement compared to PVA fiber-doped cement-based materials in mechanical properties. Therefore, developing a new inorganic-organic composite fiber material formula can simplify the fiber preparation and subsequent grafting process, reduce energy consumption and reduce safety hazards; and ensure that the organic component provides toughness, and the inorganic component strengthens the bonding between the fiber and the matrix. It can not only greatly improve the matrix toughness of fiber cement-based composite materials, reduce the generation of cracks, and hinder the invasion of harmful ions; it can also reduce the thermal conductivity of the fiber, and ensure the safety of the matrix to a greater extent, with good economic and environmental benefits. Summary of the invention
[0005] In view of the above technical problems in the prior art, the present invention provides a calcium silicate hydrate fiber reinforced cement-based composite material and a preparation method thereof. The present invention uses polyvinyl alcohol (PVA) as an organic template, introduces a certain amount of nano-sheet calcium silicate hydrate (CSH), and uses the mixed solution as a spinning solution after sufficient stirring, and uses a sodium sulfate aqueous solution as a coagulation bath to prepare CSH / PVA hybrid fibers with high strength and high toughness through wet spinning technology. The organic-inorganic composite fiber is used in combination with cement-based materials to solve the technical problems of easy cracking and high brittleness of concrete in the prior art.
[0006] The technical solution for achieving the purpose of the present invention is as follows:
[0007] A method for preparing a calcium silicate hydrate fiber reinforced cement-based composite material comprises the following steps:
[0008] (1) Synthesize dry CSH powder;
[0009] (2) CSH and anhydrous ethanol are uniformly mixed by mechanical stirring, and then the structure of calcium silicate hydrate is destroyed by ultrasonic dispersion; then, the supernatant is obtained by static separation, and nano-sheet CSH is obtained by suspension evaporation and drying;
[0010] (3) the nanosheet CSH was dispersed in deionized water by mechanical stirring, and then PVA was added and dissolved in water under heating and stirring conditions at 95±5°C, and after thorough mixing, the temperature was lowered to 60±5°C and stirred to remove bubbles, thereby obtaining a mixed solution as a spinning solution;
[0011] (4) using a saturated sodium sulfate aqueous solution at 60° C. as a coagulation bath, spinning the spinning solution using a wet spinning technique to obtain primary fibers;
[0012] (5) stretching the as-spun fibers twice, first stretching the as-spun fibers at 60°C, and then stretching the fibers after the first stretching at 100°C, to obtain high-strength and high-tenacity CSH / PVA hybrid fibers;
[0013] (6) Using cement, stone, sand, water, a water reducing agent, and the CSH / PVA hybrid fiber obtained in step (5) as raw materials, forming a calcium silicate hydrate fiber reinforced cement-based composite material.
[0014] Specifically, in step (1), the CSH powder synthesis method is as follows: calcium oxide powder and nano-silicon dioxide powder are uniformly dispersed in deionized water with a calcium-silicon ratio of 1.0 and a water-solid ratio of 15, and uniformly mixed and reacted for 14 days in a glove box isolated from carbon dioxide. Then, 50% ethanol solution is used for filtration and washing to remove excess ions, and the mixture is dried in a vacuum drying oven at 45° C. to constant weight, and ground through a 200-mesh sieve to obtain CSH powder.
[0015] Specifically, in step (2), the mass ratio of anhydrous ethanol to CSH is 100. To ensure that the structure of CSH is fully broken up, the speed of mechanical stirring is 250-400 rpm, and the stirring time is 7 days; the ultrasonic dispersion time is 12 hours, and an ice bath is used to ensure that the ultrasonic temperature does not exceed 30°C to prevent the deposition of sheet particles caused by temperature rise; the static precipitation time is 1-3 days. The two-dimensional plane size of the nano-sheet CSH is less than 300nm.
[0016] Preferably, in step (3), in the mixed solution, the concentration of PVA is 12-17wt%, the concentration of nano-sheet CSH is 0.5-3wt%, the mixture is stirred for 24 hours, and the bubble removal time is controlled within 1-2 hours. The spinning solution prepared under the above conditions contains less bubbles and has good spinnability; the CSH in the synthesized fiber is evenly distributed, and the cross-linking effect with PVA improves the strength and temperature resistance of the fiber.
[0017] Furthermore, in step (5), the mass fractions of each raw material in the calcium silicate hydrate fiber reinforced cement-based composite material are as follows:
[0018] Cement: 100 parts;
[0019] Crushed stone: 150-300 parts;
[0020] Quartz sand: 100-200 parts;
[0021] Water: 25-60 parts;
[0022] Water reducing agent: 0.1-0.25 parts;
[0023] and CSH / PVA hybrid fibers accounting for 0.3-2% of the total volume of the calcium silicate hydrate fiber reinforced cement-based composite material.
[0024] Specifically, the steps of forming the calcium silicate hydrate fiber reinforced cement-based composite material of the present invention mainly include:
[0025] S1: Add cement, gravel, quartz sand and CSH / PVA hybrid fibers into a stirring pot and continue stirring until the fibers are evenly dispersed without agglomeration;
[0026] S2: adding the water reducer into the water and mixing evenly, then adding the water reducer into the stirring pot in step S1 and continuing stirring until the slurry fluidity reaches the required level;
[0027] S3: Pour the evenly stirred slurry into a mold for forming, and perform standard curing after taking it out.
[0028] The beneficial effects of the present invention are:
[0029] The present invention firstly mixes the hydration product inorganic CSH into PVA in the form of nano-sheets to prepare an inorganic-organic composite fiber material, and then adds CSH / PVA hybrid fiber into cement slurry to further prepare a fiber cement-based composite material. The nano-sheet CSH participates in the formation process of PVA fiber, which not only helps to improve the strength of the fiber, but also strengthens the bonding effect between the fiber and the cement matrix by inducing the accumulation of hydration products, greatly improving the toughness of the cement material; at the same time, the lower thermal conductivity coefficient of CSH / PVA hybrid fiber is conducive to ensuring the stability of the structure, comprehensively improving the durability and safety of concrete materials, and can meet the safety requirements of various projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 These are the actual pictures of the nanosheet CSH and CSH / PVA hybrid fibers in Example 1 and Example 2, wherein (a) is the untreated original CSH powder, (b) is the nanosheet CSH, (c) is the scanning electron microscope image of the CSH / PVA hybrid fiber, (d) is the X-ray diffraction spectrum of the original CSH and the nanosheet CSH, (e) is the energy dispersive X-ray spectrum of the CSH / PVA hybrid fiber, and (f) is the actual picture of the CSH / PVA hybrid fiber.
[0031] Figure 2 and 3 is the fracture toughness of Example 1, Example 2, Comparative Example 2 and Comparative Example 3, wherein Figure 2 are the load-displacement curves of the four. Figure 3 The fracture toughness comparison of the four. DETAILED DESCRIPTION
[0032] In order to make the technical solutions in the present invention better understood by the persons skilled in the art, the technical solutions in the embodiments of the present invention are described clearly and completely below, and the described embodiments are only a part of the embodiments of the present invention. The present invention is further described below in conjunction with the accompanying drawings.
[0033] Embodiment 1:
[0034] (1) Synthesize dry CSH powder;
[0035] (2) 5 g of C-SH and 500 g of anhydrous ethanol were uniformly mixed by mechanical stirring for 7 days, and then the suspension was ultrasonically dispersed for 12 h at a temperature not exceeding 30 °C, and then allowed to stand for 2 days, the supernatant was separated, and nanosheet CSH was obtained by suspension evaporation drying;
[0036] (3) 1 g of nanosheet CSH was dispersed in 82 g of deionized water by mechanical stirring, and then PVA (17 g) was added and dissolved in water under heating and stirring conditions at 95±5°C. After thorough mixing, the temperature was lowered to 60±5°C and stirred to remove bubbles, thereby obtaining a mixed solution with a PVA concentration of 17 wt% and a CSH concentration of 1 wt% as a spinning solution;
[0037] (4) using a saturated sodium sulfate aqueous solution at 60° C. as a coagulation bath, spinning the spinning solution using a wet spinning technique to obtain primary fibers;
[0038] (5) stretching the as-spun fibers twice, first stretching the as-spun fibers at 60°C, and then stretching the fibers after the first stretching at 100°C, to obtain high-strength and high-tenacity CSH / PVA hybrid fibers;
[0039] (6) Using cement, stone, sand, water, water reducing agent, and the CSH / PVA hybrid fiber obtained in step (5) as raw materials, high-toughness concrete is obtained by molding. The proportions of the raw materials (by weight) are shown in Table 1.
[0040] Table 1
[0041] cement gravel Quartz sand water Water reducing agent CSH / PVA hybrid fiber 100 265 150 36 0.14 0.5% of the total volume of high toughness concrete
[0042] Among them, the cement is ordinary Portland cement with a grade of 42.5; the coarse aggregate adopts a grading of 5 to 25 mm; the quartz sand adopts standard sand; the water reducer is a polycarboxylic acid type high-efficiency water reducer; the nominal length of the PVA fiber is 6 to 9 mm, and the equivalent diameter is 12 to 18 μm.
[0043] Embodiment 2:
[0044] (1) Synthesize dry CSH powder;
[0045] (2) 5 g of C-SH and 500 g of anhydrous ethanol were uniformly mixed by mechanical stirring for 7 days, and then the suspension was ultrasonically dispersed for 12 h at a temperature not exceeding 30 °C, and then allowed to stand for 2 days, the supernatant was separated, and nanosheet CSH was obtained by suspension evaporation drying;
[0046] (3) 2 g of nano-sheet CSH was dispersed in 82 g of deionized water by mechanical stirring, and then PVA (16 g) was added and dissolved in water under heating and stirring conditions at 95±5°C. After thorough mixing, the temperature was lowered to 60±5°C and stirred to remove bubbles, thereby obtaining a mixed solution with a PVA concentration of 17 wt% and a CSH concentration of 1 wt% as a spinning solution;
[0047] (4) using a saturated sodium sulfate aqueous solution at 60° C. as a coagulation bath, spinning the spinning solution using a wet spinning technique to obtain primary fibers;
[0048] (5) stretching the as-spun fibers twice, first stretching the as-spun fibers at 60°C, and then stretching the fibers after the first stretching at 100°C, to obtain high-strength and high-tenacity CSH / PVA hybrid fibers;
[0049] (6) Using cement, stone, sand, water, water reducing agent, and the CSH / PVA hybrid fiber obtained in step (5) as raw materials, high-toughness concrete is molded. The raw material proportions (by weight) are shown in Table 2.
[0050] Table 2
[0051] cement gravel Quartz sand water Water reducing agent CSH / PVA hybrid fiber 100 265 150 36 0.14 0.5% of the total volume of high toughness concrete
[0052] Among them, the cement is ordinary Portland cement with a grade of 42.5; the coarse aggregate adopts a grading of 5 to 25 mm; the quartz sand adopts standard sand; the water reducer is a polycarboxylic acid type high-efficiency water reducer; the nominal length of the PVA fiber is 6 to 9 mm, and the equivalent diameter is 12 to 18 μm.
[0053] Figure 1 The morphology of the nanosheet CSH in Example 1 and Example 2 and the actual picture of the prepared CSH / PVA hybrid fiber. It can be seen that after step (2) in Examples 1 and 2, the CSH layered structure is destroyed, and the nanosheet CSH can be well combined with PVA to form micro-nano designable fibers.
[0054] Comparative Example 1:
[0055] (1) PVA (18 g) and 82 g of water were heated and stirred at 95° C. for 24 h. After the solution was clarified, the temperature was lowered to 60° C. and stirred for 1 h to remove bubbles, thereby obtaining a spinning solution with a PVA concentration of 18 wt %;
[0056] (2) using a saturated sodium sulfate aqueous solution at 60° C. as a coagulation bath, spinning the spinning solution using a wet spinning technique to obtain primary fibers;
[0057] (3) The as-spun fibers are stretched twice, first at 60°C, and then at 100°C after the first stretch, to obtain pure PVA fibers.
[0058] Comparative Example 2:
[0059] The ingredients are prepared according to the traditional C50 concrete materials, and the proportions of each raw material (by weight) are shown in Table 3.
[0060] Table 3
[0061] cement gravel Quartz sand water Water reducing agent 100 265 150 36 0.12
[0062] Among them, the cement is ordinary Portland cement with grade 42.5; the coarse aggregate adopts grading of 5 to 25 mm; the quartz sand adopts standard sand; and the water reducer is a polycarboxylic acid type high-efficiency water reducer.
[0063] The molding steps include:
[0064] S1: Add cement, crushed stone and quartz sand into a mixing pot and stir continuously;
[0065] S2: adding the water reducer into the water and dispersing it evenly, then adding it into the stirring pot in step S1 and continuing stirring until the slurry fluidity reaches the requirement;
[0066] S3: Pour the evenly stirred slurry into a mold for molding, take it out and perform standard curing to obtain a test block of 100 mm × 100 mm × 400 mm.
[0067] Comparative Example 3:
[0068] The ingredients are prepared according to the traditional high-toughness concrete materials, and the proportion of each raw material (by weight) is shown in Table 4.
[0069] Table 4
[0070] cement gravel Quartz sand water Water reducing agent Commercial PVA Fiber 100 265 150 36 0.14 0.5% of the total volume of high toughness concrete
[0071] Among them, cement is ordinary Portland cement with a grade of 42.5; coarse aggregate is 5-25mm graded; quartz sand is standard sand; water reducer is polycarboxylic acid type high-efficiency water reducer; PVA fiber has a nominal length of 8-15mm, an equivalent diameter of 30-45μm, and a tensile strength of ≥1100N / mm 2 .
[0072] The molding steps include:
[0073] S1: Add cement, crushed stone, quartz sand and fiber into a mixing pot and stir continuously;
[0074] S2: adding the water reducer into the water and dispersing it evenly, then adding it into the stirring pot in step S1 and continuing stirring until the slurry fluidity reaches the requirement;
[0075] S3: Pour the evenly stirred slurry into a mold for molding, take it out and perform standard curing to obtain a test block of 100 mm × 100 mm × 400 mm.
[0076] The basic properties and mechanical properties of the fibers prepared in Example 1, Example 2 and Comparative Example 1 were measured, and the results are shown in Table 5. Compared with the pure PVA fiber of Comparative Example 1, the incorporation of nanosheet CSH in Examples 1 and 2 can improve the tensile strength and modulus of the hybrid fibers, and at the same time reduce the thermal conductivity of the fibers.
[0077] Table 5
[0078]
[0079] Depend on Figure 2 The fracture toughness test results of the fiber cement-based composites show that the fracture toughness of Examples 1 and 2 are improved compared with Comparative Examples 2 and 3. The addition of CSH / PVA fibers is beneficial to improving the toughness of the cement matrix, and the improvement effect is more than doubled.
Claims
1. A method for preparing CSH / PVA hybrid fiber, characterized in that: The following steps are involved: (1) Synthesize dry CSH powder; (2) CSH is uniformly mixed with anhydrous ethanol, and then the structure of calcium silicate hydrate is destroyed by ultrasonic dispersion; then, the supernatant is obtained by standing and separation, and then dried to obtain nano-sheet CSH; (3) dispersing the nanosheet CSH in deionized water, then adding PVA and heating and stirring at 95±5°C, and after thorough mixing, cooling to 60±5°C and stirring to remove bubbles, to obtain a mixed solution as a spinning solution; (4) using a saturated sodium sulfate aqueous solution at 60° C. as a coagulation bath, spinning the spinning solution using a wet spinning technique to obtain primary fibers; (5) The as-spun fibers were stretched twice, first at 60°C, and then at 100°C, to obtain CSH / PVA hybrid fibers.
2. The preparation method according to claim 1, characterized in that: In step (1), the calcium-silicon ratio of the CSH powder is 1.0 and the water-solid ratio is 15.
3. The preparation method according to claim 1, characterized in that: In step (2), the two-dimensional plane size of the nanosheet CSH is less than 300 nm.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of anhydrous ethanol to CSH is 100.
5. The preparation method according to claim 1, characterized in that: In step (3), in the mixed solution, the concentration of PVA is 12-17 wt %, and the concentration of nano-sheet CSH is 0.5-3 wt %.
6. The preparation method according to claim 1, characterized in that: In step (4), during the spinning process, the spinning solution injection speed is 50-100 μL / min, the spinneret diameter is 0.08-0.16 mm, and the coagulation bath temperature is 60±5°C.
7. CSH / PVA hybrid fiber obtained according to the preparation method according to any one of claims 1 to 6.
8. A method for using the CSH / PVA hybrid fiber according to claim 7 in preparing calcium silicate hydrate fiber reinforced cement-based composite materials to improve the toughness of the cement matrix and reduce the thermal conductivity.
9. The application method according to claim 7, characterized in that: The following steps are involved: 1) Weigh cement, crushed stone, quartz sand, water, water reducing agent, and CSH / PVA hybrid fiber according to mass fractions; 2) Add cement, gravel, quartz sand and shear-dispersed CSH / PVA hybrid fibers into a stirring pot and continue stirring for 2 to 4 minutes until uniform; 3) adding the water reducer into the water and dispersing it evenly, then adding it into the stirring pot and continuing stirring until the slurry fluidity reaches the requirement, thus obtaining the calcium silicate hydrate fiber reinforced cement-based composite material.
10. The application method according to claim 9, characterized in that: The CSH / PVA hybrid fiber accounts for 0.3-2% of the total volume of the calcium silicate hydrate fiber reinforced cement-based composite material.
